FUND MOBILISATION, ALLOCATION AND UTILISATION AS PREDICTORS OF STUDENTS’ ACHIEVEMENT IN PUBLIC SECONDARY SCHOOLS IN NIGERIA, 2001 -2005 (2013)
There have been low mobilisation and poor allocation of funds to education in Nigeria. Studies have shown over the years that, there have been fluctuations in the budgetary allocation to education. The attendant effects of this are late payment of salaries, inadequate staff and dilapidated infrastructure. This therefore, resulted in repeated poor students’ achievement in the West African Senior School Certificate Examination in public secondary schools in Nigeria. Though studies have been conducted on fund allocation and utilisation, only few have been on fund mobilisation. This study, therefore, investigated the relationship among fund mobilisation, allocation and utilisation as predictors of students’ achievement in public secondary schools in Nigeria from 2001-2005. The study adopted descriptive survey design of ex-post facto type. A total of 1,826 public secondary schools from Lagos, Enugu, Akwa-Ibom, Kano, Bauchi and Nasarawa states representing each of the six geo-political zones were sampled for the study using multi-stage sampling technique. Secondary data were used for the study. The Senior Certificate Examination results of 1,413,454 students from the sampled states were used for the analysis. Four research questions were answered and five hypotheses tested at 0.05 level of significance. Data were analysed using Descriptive Statistics, Pearson Product Moment Correlation and Multiple Regression. There was an upward trend in fund allocation to education in Lagos state from 21.58% to 25%, Akwa Ibom state 6.6% to 13.1%, Nasarawa state 9.0% to 16.2%, Bauchi state 9.50% to 10.05% and Kano state 15.2% to 18%. There was a downward trend in fund allocation to education in Enugu state from 22.7% to 22.3%.There was an upward trend in fund allocation to secondary education in Lagos state from 26.5% to 28.4%, Enugu state 14.2% to 24.7% , Bauchi state 8.0% to 9.8% and Nasarawa state 9.9% to 32.7%. However, there was a downward trend in fund allocation to secondary education in Akwa Ibom state 7.5% to 3.5% and Kano state 72.1% to 46.8% states. Fund mobilisation, allocation and utilisation jointly accounted for 46.9% variance in predicting students’ achievement in public secondary schools (R = 0.687; F(3,1822) = 46.27, p < 0.05). The contributions of each variable to students’ achievement was: fund allocation (β=0.287, t = 3.252, p <.05), fund mobilisation (β = 0.212, t = 3.494, p < 0.05), utilisation of financial resources (β = 0.301, t = 4.045, p < 0.05), student / teacher ratio (β= 0.156, t = 2.455, p < 0.05). UNIVERSITY OF IBADAN LIBRARY iv Mobilisation, allocation and utilisation of funds have improved students’ achievement. Government should, therefore, allocate more funds to secondary education so that all facilities that would improve the students’ achievement are made available. Ministries of education and principals of schools should broaden their revenue generation capacities and utilise the funds available to them properly to improve students’ achievement. Key words: Fund mobilisation, Fund allocation, Fund utilisation, Students’ achievement, Secondary school Word count: 460